The Effect Of Training, Work Motivation, And Leadership Style On Employee Performance At Pt. Bank Rakyat Indonesia (Persero) Tbk Pematang Siantar Branch Office - Sinaga, Erik Samola; Lahindah, Laura (Universitas Dehasen Bengkulu, 2025)
This study aims to analyze the influence of training, work motivation, and leadership style on employee performance, both partially and simultaneously, at PT. Bank Rakyat Indonesia (Persero) Tbk, Pematang Siantar Branch Office. The research method used was a quantitative approach with multiple linear regression analysis. The sample size for this study was 126 respondents, consisting of various positions, such as marketing, customer service, tellers, and back office. The analysis results indicate that partially, training, work motivation, and leadership style have a positive and significant effect on employee performance. Simultaneously, these three independent variables also significantly influence performance. This is indicated by the calculated F-value of 10.106 > F-table 2.68 and a significance level of 0.000 < 0.05. These findings confirm that structured training, high work motivation, and effective leadership can improve employee quality and productivity. This study implies that organizations need to consistently strengthen training, build internal motivation, and implement adaptive leadership styles to optimize employee performance in facing dynamic work challenges.